2019
DOI: 10.1111/cote.12423
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carboxylated graphene oxide nanosheets/polysulphone hollow fibre separation membranes with improved separation and dye adsorption properties

Abstract: Novel hollow fibre polysulphone (PSF) separation membranes were prepared via the incorporation of carboxylated graphene oxide (cGO) in membrane matrix during the dry‐wet spinning process to improve the membrane performance of water flux and dye adsorption. The surface composition and morphology of the prepared cGO‐incorporated hollow fibre membranes were characterised by means of Fourier Transform–infrared spectra and scanning electron microscopy. The effects of different cGO contents on membrane surface hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Graphene and its derivatives or composites can effectively be used as adsorbents, 2,3 however, many studies have shown a correlation between the amount of oxidation on graphene and its adsorption capabilities 19 whereas graphene with a high degree of oxidation or having many active sites, has high hydrophilicity and that enhances its interaction with contaminants. 20 A signicant obstacle in the wastewater treatment process is the widespread separation and recycling of nanomaterials. A possible solution is the support of graphene on a polymeric matrix, such as polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene and its derivatives or composites can effectively be used as adsorbents, 2,3 however, many studies have shown a correlation between the amount of oxidation on graphene and its adsorption capabilities 19 whereas graphene with a high degree of oxidation or having many active sites, has high hydrophilicity and that enhances its interaction with contaminants. 20 A signicant obstacle in the wastewater treatment process is the widespread separation and recycling of nanomaterials. A possible solution is the support of graphene on a polymeric matrix, such as polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and its derivatives or composites can effectively be used as adsorbents, 2,3 however, many studies have shown a correlation between the amount of oxidation on graphene and its adsorption capabilities 19 whereas graphene with a high degree of oxidation or having many active sites, has high hydrophilicity and that enhances its interaction with contaminants. 20…”
Section: Introductionmentioning
confidence: 99%